Asymmetric dimethylarginine targets MAPK pathway to regulate insulin resistance in liver by activating inflammation factors. Issue 5 (2nd December 2018) - Huang, Shan; Xu, Yong; Peng, Wen‐Fang; Cheng, Jie; Li, Hui‐Hua; Shen, Li‐Sha; Xia, Li‐Li
Abstract: Insulin resistance is associated with impaired glucose uptake and altered protein kinase B (Akt) signaling. Previous studies have suggested asymmetric dimethylarginine (ADMA) and inflammation are two distinguish factors that correlate with insulin resistance (IR). How ADMA and inflammation factors interact and synchronize in the regulation of IR in liver remain to be elucidated. In this study, we systematically investigated whether ADMA is involved in IR using primary hepatocytes, if yes, by via which molecular mechanism. Our results demonstrated that ADMA inhibits insulin sensitivity in a concentration‐dependent manner by activating inflammation factors tumor necrosis factor (TNF)‐α, interleukin (IL)‐1, and IL‐6 in primary hepatocytes. Further analysis revealed that mitogen‐activated protein kinase (MAPK) signaling pathway act downstream of ADMA and inflammation factors, and inhibition of MAPK pathway rescued the IR. Furthermore, metformin effects has been found which could reverse ADMA‐induced IR by suppressing MAPK signaling pathway. To our knowledge, we, for the first time, unveiled the complicated regulatory network and interactions among ADMA, inflammation, and MAPK signaling pathway, which advanced current research on the development and regulation of IR in liver. This study also certainly provided novel insights on comprehensive diagonistics roles of ADMA as a potential biomarker. Abstract : We, for the first time, unveiled the complicated regulatory network and interactions among asymmetric dimethylarginine (ADMA), inflammation, and mitogen‐activated protein kinase signaling pathway, which advanced current research on the development and regulation of insulin resistance in liver. This study also certainly provided novel insights on comprehensive diagonistics roles of ADMA as a potential biomarker.